COVID-19 Contact Tracing and Data Protection Can Go Together - Abeler, Johannes; Bäcker, Matthias; Buermeyer, Ulf; Zillessen, Hannah (JMIR mHealth and uHealth, 2020)
We discuss the implementation of app-based contact tracing to control the coronavirus disease (COVID-19) pandemic and discuss its data protection and user acceptability aspects.We discuss the implementation of app-based contact tracing to control the coronavirus disease (COVID-19) pandemic and discuss its data protection and user acceptability aspects.